GC-MS ANALYSIS OF ACANTHOPHORA SPICIFERA - G. FLORA; S. MARIA VICTORIAL RANI (International Journal of Pharma and Bio Sciences, 2013)
Acanthophora spicifera is one of the bioactive compound rich seaweed, which exhibit potent antitumor and antibacterial activity against human cancer cell lines and bacteria. In the present study, the methanolic extract of A. spicifera has been subjected to GC-MS analysis. Twenty four chemical constituents have been identified. The major constituents are octanol, piperazine, benzoic acid and octadecenoic acid. These compounds are invariably having pesticidal, antimicrobial and anti-inflammatory properties.